Exercise in the heat: challenges and opportunities - Maughan, R.; Shirreffs, S. (Journal of Sports Sciences, 2004)
Exercise in the heat poses a formidable challenge to the body's ability to control its internal environment due to the high rates of metabolic heat production and heat gain by physical transfer from the environment. In an attempt to restrict the rise in core temperature, an increased rate of sweat secretion onto the skin is invoked. This may limit the rise in core temperature, and can prolong the time before a limiting temperature is attained, but it does so at the cost of a loss of body water and electrolytes. The effects of the diminished blood volume are offset to some extent by cardiovascular adaptations, including an increased heart rate and an increased peripheral resistance, but these are insufficient to maintain functional capacity when blood volume is reduced. Prior dehydration will impair performance in both prolonged exercise and short-term high-intensity exercise. Athletes living and training in the heat may experience chronic hypohydration due to inadequate replacement of fluid losses. The negative consequences of exercise in the heat are attenuated to some extent by a period of adaptation, and by the ingestion of water or other appropriate fluids. Optimum fluid replacement strategies will depend on the exercise task, the environmental conditions and the individual physiological characteristics of the athlete. Manipulation of pre-exercise body temperature can also influence exercise performance and may be a strategy that can be used by athletes competing in stressful environments.